2015
DOI: 10.1002/anie.201502104
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Pathways for NO Electroreduction on Pt(111) from First Principles

Abstract: The mechanism of nitric oxide electroreduction on Pt(111) is investigated using a combination of first principles calculations and electrokinetic rate theories. Barriers for chemical cleavage of N-O bonds on Pt(111) are found to be inaccessibly high at room temperature, implying that explicit electrochemical steps, along with the aqueous environment, play important roles in the experimentally observed formation of ammonia. Use of explicit water models, and associated determination of potential-dependent barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
128
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 32 publications
4
128
0
Order By: Relevance
“…30 Even at the saturated coverages, however, we found that formation of the trans-(NO) 2 dimer on Pt(100) requires a 1.32 eV kinetic barrier, indicating that this reaction will not occur at room temperature.…”
Section: Ammonia Formation At Saturated Surface Coveragementioning
confidence: 73%
See 4 more Smart Citations
“…30 Even at the saturated coverages, however, we found that formation of the trans-(NO) 2 dimer on Pt(100) requires a 1.32 eV kinetic barrier, indicating that this reaction will not occur at room temperature.…”
Section: Ammonia Formation At Saturated Surface Coveragementioning
confidence: 73%
“…52 Corrections to surface adsorbate energies from hydrogen bonding effects are applied, as discussed in a previous study. 30 Reaction barriers for N-O bond dissociation and protonation of intermediates are modeled within a 3 × 3 unit cell and determined using the climbing image nudged elastic band method (CI-NEB) implemented by Henkelman and co- workers. 53 A hydrogen shuttling model is employed for protonation barrier calculations.…”
Section: Acs Catalysismentioning
confidence: 99%
See 3 more Smart Citations